NOX1 Regulates Collective and Planktonic Cell Migration: Insights From Patients With Pediatric-Onset IBD and NOX1 Deficiency. Issue 8 (17th February 2020) - Khoshnevisan, Razieh; Anderson, Michael; Babcock, Stephen; Anderson, Sierra; Illig, David; Marquardt, Benjamin; Sherkat, Roya; Schröder, Katrin; Moll, Franziska; Hollizeck, Sebastian; Rohlfs, Meino; Walz, Christoph; et al.
Abstract: Background: Genetic defects of pediatric-onset inflammatory bowel disease (IBD) provide critical insights into molecular factors controlling intestinal homeostasis. NOX1 has been recently recognized as a major source of reactive oxygen species (ROS) in human colonic epithelial cells. Here we assessed the functional consequences of human NOX1 deficiency with respect to wound healing and epithelial migration by studying pediatric IBD patients presenting with a stop-gain mutation in NOX1 . Methods: Functional characterization of the NOX1 variant included ROS generation, wound healing, 2-dimensional collective chemotactic migration, single-cell planktonic migration in heterologous cell lines, and RNA scope and immunohistochemistry of paraffin-embedded patient tissue samples. Results: Using exome sequencing, we identified a stop-gain mutation in NOX1 (c.160C>T, p.54R>*) in patients with pediatric-onset IBD. Our studies confirmed that loss-of-function of NOX1 causes abrogated ROS activity, but they also provided novel mechanistic insights into human NOX1 deficiency. Cells that were NOX1-mutant showed impaired wound healing and attenuated 2-dimensional collective chemotactic migration. High-resolution microscopy of the migrating cell edge revealed a reduced density of filopodial protrusions with altered focal adhesions in NOX1-deficient cells, accompanied by reduced phosphorylation of p190A. Assessment of single-cell planktonic migration toward an epidermal growth factor gradient showed that NOX1 deficiency is associated with altered migration dynamics with loss of directionality and altered cell-cell interactions. Conclusions: Our studies on pediatric-onset IBD patients with a rare sequence variant in NOX1 highlight that human NOX1 is involved in regulating wound healing by altering epithelial cytoskeletal dynamics at the leading edge and directing cell migration. Abstract : Loss-of-function mutations in human NOX1 result in altered intestinal epithelial reactive oxygen species production. We show that loss of NOX1-mediated reactive oxygen species production is associated with complex alterations of cell migration dynamics important for epithelial wound repair.